3D modelling of electrostatic force distance curve between the AFM probe and dielectric surface - Boularas, A. (2014)
Techniques derived from the near-field microscopies and particularly the Atomic Force Microscopy (AFM) are presented as alternative techniques for measurement of space charge compared to classical techniques due to their high sensitivity to the electrostatic force and a better resolution (≈ nm). One of the AFM derivative techniques which allow obtaining information on the charge state of the dielectric materials is based on the technique of Force Distance Curves (FDC) obtained by cycle of approach and retracts between the AFM probe and the dielectric. In this paper, three-Dimensional (3D) simulation results for the electrostatic force between an Atomic Force Microscope (AFM) tip and the surface of a dielectric are presented for different AFM tip geometries. The first aim is to analyse the effect of the geometric parameter on force-distance curves without contribution of the cantilever as AFM detection mode for electrostatic charges. At the second time the sensor is composed of a cantilever supporting a conical tip terminated by a spherical apex, we investigate in a second step is to see the effect of the cantilever on force distance curve. Simulation results are shown and compared with experimental data in order to validate our approach.